By design: negotiating flexible learning in the built environment discipline - Richard Tucker; Gayle Morris (Association for Learning Technology, 2012)
The term ‘flexible education’ is now firmly entrenched within Australian higher education discourse, yet the term is a contested one imbued with a multiplicity of meanings. This paper describes a process designed to elucidate how the idea of flexible education can be translated into teaching models that are informed by the specific demands of disciplinary contexts. The process uses a flexible learning ‘matching’ tool to articulate the understandings and preferences of students and academics of the Built Environment to bridge the gap between student expectations of flexibility and their teacher's willingness and ability to provide that flexibility within the limits of the pedagogical context and teaching resources. The findings suggest an informed starting point for educators in the Built Environment and other creative disciplines from which to traverse the complexities inherent in negotiating flexibility in an increasingly digital world.